Digital Twins in the Construction Industry: A Perspective of Practitioners and Building Authority - Ammar, Ashtarout; Nassereddine, Hala; AbdulBaky, Nadine; AbouKansour, Anwar; Tannoury, Juliano; Urban, Harald; Schranz, Christian (Frontiers in Built Environment, 2022)
As the notion of data-driven analytics and turning data into action is becoming more salient in the construction industry, researchers and practitioners have recently devoted considerable effort to investigate the digital transformation of the industry. Along this journey, Digital Twin has been introduced to the industry as a concept that holds the promise to challenge the status-quo and address long standing problems of productivity, efficiency, and value. While this concept is becoming more familiar among practitioners, there is a lack of universal definitions of what the Digital Twin of a construction project is. Additionally, while identifying the purpose of Digital Twin is recognized as the first step in implementing Digital Twins, there is little discussion on the perception of construction practitioners of the extent to which Digital Twin can deliver value. To address these research gaps and building on the existing work on Digital Twins in the context of the construction industry, this paper first proposes a definition of the Digital Twin of a construction project. Next, a series of semi-structured interviews are conducted with nine construction practitioners to understand their perceptions on the use and challenges of Digital Twins. Thematic analysis is then used to analyze interview data and summarize Digital Twins applications, capabilities, and challenges. Forty direct applications were identified and grouped into nine capabilities. Digital Twins capabilities of Increase Transparency of Information and Real-Time Monitoring, Analysis, and Feedback were the most discussed with a total of eight applications each, followed by Better Stakeholder Collaboration which had seven applications. The discussion on challenges led to the identification of 34 challenges to implementing Digital Twin, grouped into six categories coded through thematic analysis. The category on Data Understanding, Preparation, and Usage Challenges was found to be the most critical for the interviewees. Additionally, the paper presents a case study on how building authority can be integrated into Digital Twins and leverage its use throughout the lifecycle of a building. Future work can further investigate the challenges and develop prototypes that can help in quantifying the benefits of implementing Digital Twins on a Construction Project.